2015
DOI: 10.4081/dr.2015.5960
|View full text |Cite
|
Sign up to set email alerts
|

An epidemiological study of 97 cases of primary cicatricial alopecia in Iran

Abstract: Cicatricial alopecia can produce major psychosocial disturbance. This study aimed to evaluate epidemiological features of primary cicatricial alopecia (PCA). Epidemiological and histological types of scarring alopecia were determined. The chi-squared test and t-test were performed to examine the relationship between different variables using SPSS 16. A total of 97 cases, 35 (36.1%) men and 62 (63.9%) women, with an average age of 37 (SD=12.7), were included in this study. The female/male (F/M) ratio was 1.7:1 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
1
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(31 citation statements)
references
References 12 publications
4
23
1
2
Order By: Relevance
“…These results suggest that the female preponderance among Caucasian patients may be attributed to lymphocytic concentrations, which were fourfold higher than neutrophils in previous reports . In contrast, a different study showed male predominance among PCA patients . The female : male ratio in the study was 1.7:1, and the ratio was 1.9:1 for the lymphocytic subtype and 1:1.5 for the neutrophilic group.…”
Section: Discussioncontrasting
confidence: 63%
See 3 more Smart Citations
“…These results suggest that the female preponderance among Caucasian patients may be attributed to lymphocytic concentrations, which were fourfold higher than neutrophils in previous reports . In contrast, a different study showed male predominance among PCA patients . The female : male ratio in the study was 1.7:1, and the ratio was 1.9:1 for the lymphocytic subtype and 1:1.5 for the neutrophilic group.…”
Section: Discussioncontrasting
confidence: 63%
“…3 In contrast, a different study showed male predominance among PCA patients. 6 The female : male ratio in the study was 1.7:1, and the ratio was 1.9:1 for the lymphocytic subtype and 1:1.5 for the neutrophilic group. In addition, we observed a high prevalence of neutrophilic PCA.…”
Section: Discussionmentioning
confidence: 68%
See 2 more Smart Citations
“…Mean age at the time of presentation in our patients was almost similar to other studies in our region; however, f/m ratio is higher than Abedini et al . but similar to Beheshtiroy . In most surveys, LPP was more common in females .…”
Section: Discussionsupporting
confidence: 88%